Evaluation Of Jatropha Oil For The Production Of Polysydroxyalkanoates (PHAs) By Cupriavidus Necator H16 - Ng , Ko Sin (2011)
Jatropha oil, a non-edible vegetable oil, could serve as an alternative substrate to food grade oils for polyhydroxyalkanoates (PHAs) production. Jatropha oil contains oleic acid (42%), linoleic acid (35%) and palmitic acid (17%) as the major fatty acid constituents. Cupriavidus necator H16 accumulated 87 wt% of poly(3-hydroxybutyrate) [P(3HB)] from 13.1 g/L of cell dry weight (CDW) when 12.5 g/L of jatropha oil and 0.54 g/L of urea were used. Lipase activity was detected in the initial stages of P(3HB) production, when 1 g/L of jatropha oil was added to the preculture medium. However, the addition of oil in preculture did not affect final CDW and P(3HB) accumulation.